PERANCANGAN SISTEM BANTUAN JARING PENGAMAN SOSIAL BERBASIS WEB DI KECAMATAN MAOSPATI, KABUPATEN MAGETAN - Agus Sujarwadi (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2022)
The Maospati District Office is a sub-district office located in the Maospati area, Magetan, East Java. This sub-district office is engaged in community services, such as activating Electronic Identity Cards (E-KTP), making Family Cards, Community Complaints, Poor Community Assistance Services and online administrative document retrieval services. This sub-district office has an information system for processing data on the assistance of the Social Safety Net (JPS) which is still in manual form and has not been automated so that it is slow in the process of collecting data for additions, changes, and deletions of data. The purpose of making the application of the Community Safety Net Assistance Data Management System at the Maospati District Office is to be able to help provide alternative data storage to databases in Maospati District. The method in this research by utilizing certain techniques, namely field studies and literature studies. The result of this research is the Design of Social Safety Net Assistance Data Management System in Maospati District, Magetan Regency.